2020
DOI: 10.2174/0929866527666200413101017
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering of The Effect of Chemotherapeutic Agents on Human Glutathione S-Transferase Enzyme and MCF-7 Cell Line

Abstract: Background: Cancer is the disease that causes the most death after cardiovascular diseases all over the world these days. Breast cancer is the most common type of cancer among women and ranks the second among cancer-related deaths after lung cancer. Chemotherapeutics act by killing cancer cells, preventing their spread and slowing their growth. Recent studies focus on the effects of chemotherapeutics on cancer cells and new chemotherapy approaches that targeting enzymes that catalyze important metabolic react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
4
0
3
Order By: Relevance
“…The results of this study showed that both 5-FU and tamoxifen increase the GST enzyme activity. The results of this study are similar to the results of our study [6]. In a different study, it was determined that 5-FU coumarin derivatives showed a potent and totally selective inhibitory action against the target CA IX/XII enzyme activities [40].…”
Section: -Fu [Mm]supporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study showed that both 5-FU and tamoxifen increase the GST enzyme activity. The results of this study are similar to the results of our study [6]. In a different study, it was determined that 5-FU coumarin derivatives showed a potent and totally selective inhibitory action against the target CA IX/XII enzyme activities [40].…”
Section: -Fu [Mm]supporting
confidence: 90%
“…Chemotherapeutics inhibit the growth and proliferation of the tumor and other rapidly growing cells [2]. However, chemotherapeutics can damage organs such as the liver and kidneys during the treatment process, cause inhibition of various metabolic enzymes, prolong the treatment process and negatively affect the patient's well-being [3][4][5][6][7]. The fluoropyrimidine 5fluorouracil (5-FU) and its prodrug Capecitabine are widely used chemotherapeutic agent in the treatment of gastrointestinal, breast, head and neck cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Tümör hücrelerinde hayati hücresel yolları hedefleyen yeni ilaçların kullanımı, neoplastik hastalıklar için tedavi sonuçlarını önemli ölçüde iyileştirmiştir [27,28]. Bcr-Abl antagonistleri, monoklonal antikorlar ve proteazom inhibitörleri gibi ilaçlarla hematolojik malignitelerin tedavilerinde iyi sonuçlar elde edilmiştir.…”
Section: Discussionunclassified
“…Önceki çalışmalarda çeşitli toksik ajanların ROS üretimine bağlı olarak lipid peroksidayonu meydana getirdiğini ve buna bağlı olarak MDA seviyelerinde artışların olduğu bildirilmiştir [40][41][42][43][44]. Artan MDA seviyelerinin oksidatif stresin önemli bir göstergesi olduğunu ve oksidatif stresin de kalp dahil çeşitli dokularda toksisiteye yol açtığı yapılan çalışmalarda kanıtlanmıştır [28,[45][46][47] [15]. Biyolojik sistemlerdeki serbest radikallerin ortadan kaldırılması, serbest radikallere karşı önemli savunma sistemleri olarak işlev gören enzimatik ve enzimatik olmayan antioksidanlar tarafından sağlanır [48][49][50][51][52].…”
Section: Discussionunclassified
“…One of the most significant antioxidant defense systems is the glutathione (GSH) mechanism. GSH metabolism, including GST enzyme, contains a variety of enzymatic antioxidant components that are reported in several studies [5][6][7]. GST has a vital role in xenobiotic metabolism.…”
Section: Introductionmentioning
confidence: 99%